The Comprehensive Systematic Review of Use of Benzoyl Peroxide as Monotherapy or Combination Therapy for Acne - Auliani Deby Veronica; Deriel Elka Hidayat (International Medical Journal Corp. Ltd, 2026)
Introduction: Acne vulgaris is a prevalent inflammatory skin condition. Benzoyl peroxide (BPO) is a first-line topical agent, but the comparative efficacy of monotherapy versus combination regimens remains to be systematically defined. This review evaluates the significant positive clinical outcomes of BPO as monotherapy or combination therapy. Methods: A systematic screening of randomized controlled trials and vehicle-controlled studies was performed. Inclusion criteria: patients with acne vulgaris, BPO as active intervention, comparator group, and quantifiable outcomes. Data extraction focused on lesion count reductions, treatment success rates, safety, and comparative effectiveness. Results: From 80 included studies (29,592 participants), BPO monotherapy demonstrated significant superiority over vehicle: inflammatory lesion reduction 52.1% vs 34.7% and total lesion reduction 44.3% vs 27.8% (p<0.001) (1). Adapalene 0.1%/BPO 2.5% combination showed significant synergy, achieving 78.4% total lesion reduction vs BPO 52.6% (p<0.05) (8). The triple combination clindamycin phosphate 1.2%/adapalene 0.15%/BPO 3.1% (CAB) yielded treatment success rates of 51.3% vs adapalene 0.3%/BPO 2.5% 32.9% (p<0.001) (13). Inflammatory lesion reductions exceeded 75% with CAB (11,38). Adapalene 0.3%/BPO 2.5% reduced atrophic scar count by 21.7% at week 24 (p<0.0001 vs vehicle) (65). Safety profile showed mild-to-moderate local reactions; no serious BPO-related adverse events. Discussion: BPO monotherapy provides significant efficacy in mild-to-moderate acne. Combination therapies, particularly with adapalene or clindamycin, yield superior outcomes due to synergistic mechanisms. The triple combination CAB gel represents a significant advance for moderate-to-severe acne. However, most CAB evidence comes from industry-sponsored trials. Conclusion: BPO monotherapy is effective for mild acne. Combination therapy, especially with retinoids or antibiotics, is significantly more effective for moderate-to-severe disease. The triple combination offers the highest efficacy.